IMETHODS OF INTENSIFICATION OF HEAT EXCHANGE IN BIOGAS REACTORS - FINYK, Iryna (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Proposed research method intensification of heat exchange in biogas reactions using alternative energy sources. The distribution of active and passive methods of heat exchange intensification is determined. The three most effective methods of heat exchange intensification are identified: the method of flow turbulence in the adjacent areas, based on purposeful artificial creation of small dry wall zones, which is the source of additional flow turbulence; the method of flow winding inside the twisted oval tubes and at longitudinal and transverse winding of tightly packed beams and tubes; the method of controlled break-out of the boundary layer at transverse tubulars by creating turboblicators on them. It is determined that in practice the most effective is the use of combined methods of intensification. The important conditions for choosing the method of heat exchange intensification are: the amount of permissible energy costs for heat exchange intensification and the type of energy available for this energy; the task of heat exchange intensification in a particular class of equipment; the technological capacity of equipment with heat exchange intensification, availability at purchase and durability in operation of equipment; the nature of distribution, structure of thermal flows and temperature fields, in which there is a need for intensification of heat exchange. The main indicator of intensification of the heat exchange process in the equipment is found – the efficiency of the process, that is, the process should be economically profitable. From the above it appears that the intensification of heat exchange can’t be considered isolated from the necessary energy costs. The determining criterion of optimization is the efficiency of the heat exchange process at a given level of energy consumption at transfer of the working environment through the equipment. Heat exchange intensification during use of gaseous working environments is of particular importance, for which characteristic reduction of intensity of heat exchange processes and high energy consumption for removal of supports at pumping of gases is characteristic. Tasks of heat exchange intensification are usually set: to reduce the size and weight of heat exchange devices; to decrease the temperature pressure, i.e. to decrease the temperature of the walls at the given temperature of heat carrier or to increase the temperature of heat carrier at the given temperature of walls. Reduction of thickness of heat transfer wall and increase of its thermal conductivity, as well as prevention waste contamination on the wall is an obvious method of intensification of heat exchange.
Keywords: альтернативне джерело енергії.; biogas reactor; alternative energy source